E-Commerce Shop Helviah Skincare Mobile Application - Marlia Sari; Lusia Septia ER; Muhammad Junaidi (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
The rapid advancement of mobile technology has significantly transformed consumer behavior, accelerating the shift towards e-commerce as a dominant shopping method. Recognizing this trend, the Helviah Skincare Shop, a retailer specializing in skincare products, developed a mobile e-commerce application to enhance customer experience, streamline transactions, and expand its market reach. This research adopts a structured methodology encompassing problem identification, data collection, system design, development, and rigorous testing to create a user-friendly mobile platform tailored to the unique needs of skincare shoppers. The application features an intuitive product catalog, a secure payment gateway, personalized recommendations, and real-time order tracking, ensuring a seamless shopping experience. The results demonstrate a positive impact, with user feedback highlighting increased engagement, customer satisfaction, and accessibility to products. By effectively addressing consumer needs, the Helviah Skincare e-commerce application fosters customer loyalty, drives business growth, and positions the retailer as a competitive player in the e-commerce sector. This study contributes to the field of mobile commerce by showcasing a scalable solution that integrates technology and user-centered design to deliver tangible business outcomes.